Visual Culture: Antenna And Roots - Wanner, Maria Celeste de Almeida; Ornellas, Valter Luis Dantas (The Turkish Online Journal of Design Art and Communication, 2012)
The gap between the digital era in undeveloped places, in the 21st century, is an important issue to be discussed. Based in the research called Antenna and Roots, developed at the Fine Art School at the Federal University of Bahia, Brazil, called Antenna and Roots, this paper proposes a dialogue between Visual Culture and contemporary visual languages, creative process, its methodology, and how the students are encourage to investigate with low tech equipments, certain that what makes a good art work is not only the equipment, but how an artist approaches material, equipments, etc., in order to materialize ideas, along the knowledge and understand about the world they live, without illustrating theories.
Keywords: Visual culture; Görsel kültür; Visual arts; Görsel sanat; Digital image; Dijital resim; Antenna and Roots.